Distribution system state estimation with elegant PMU placements using a novel metaheuristic. (28th August 2020) - Naveenkumar, K.; Kannan, R.; Ganesan, S.; Subramanian, S.; Hariprasath, M.
In recent days, the expansion of the distribution network followed by network complexity and contingencies are noted as major issues in electric power utilities. At this juncture, there is not even a distinct constituent for handling such disturbances that occurs due to natural hazards which in turn causes a difficult situation for decision making tracked by redundant state estimation. Therefore, effective monitoring in distributed networks with phasor measuring unit (PMU) involving accurate placements and identification of numerous line outages is presented. Here, a technique using ant lion optimisation (ALO) through elite methodology (EALO) for recognising accurate PMU locations considering cascaded line outages is projected. To evaluate the effectiveness of the projected method standard IEEE systems, practical Indian utility system and polish large scale bus networks are instigated. The numerical result cares about the exact state of distribution topology in a way for improving the performance of the smart grid.